Persepsi Mahasiswa (Calon Guru) Pendidikan Vokasi Terhadap Pendidikan Science, Technology, Engineering, dan Mathematics (STEM): Perceptions of Vocational Education Students on Science, Technology, Engineering, and Mathematics (STEM) Education - Fatwa, Islami; Widya (UNIVERSITAS PENDIDIKAN GANESHA, 2023)
Abstract Science, Technology, Engineering and Mathematics (STEM) education has been widely discussed by academics, especially vocational education. However, the knowledge of vocational students/prospective teachers about Science, Technology, Engineering STEM is still limited. The purpose of this research is to describe the perceptions of prospective vocational teachers regarding STEM. This research is a descriptive research using survey method. Data collection was carried out through a questionnaire. The data collected was analyzed using percentage techniques. The results of the study show that there are positive perceptions among prospective vocational teachers about STEM education and they agree to implement the education curriculum in Indonesia. Students stated that the relationship between STEM components was integrated with each other. Most students believe that STEM is suitable for application at every level of education, STEM can link the classroom learning process with the phenomena of everyday life, STEM is suitable for Mechanical Engineering Vocational learning, STEM relates to problem solving abilities, and STEM can be a preference for choosing work in future. Write the abstract in English here. If articles in English, abstract in Indonesia language do not need to be included. Writing abbreviations and mathematical formulas in the abstract needs to be avoided.